IoT plant watering system for integrating technology and sustainability in science practicum - Fatimatuz Zahro; Eko Hariyono; Beni Setiawan; Binar Kurnia Praharani (Research and Development in Education (RaDEn), 2025)
IoT-based plant watering systems offer promising potential as practicum media to integrate technology and environmental sustainability in science education. However, science learning in schools often lacks relevant practicum tools and technology integration. This study aims to develop an IoT-based automatic plant watering system as an innovative, effective, and contextually relevant practicum medium for junior high school science. Employing the Research and Development (R&D) method with a descriptive approach, the study follows iterative stages of design, testing, and refinement to ensure the system's effectiveness and usability. The developed system allows students to monitor and control soil moisture in real-time via a mobile application, providing hands-on experience in applying STEM concepts and promoting awareness of environmental resource management. Results show the system maintains soil moisture within an optimal 40%–60% range, reduces water waste by up to 30%, and improves plant health. This innovation enhances science learning by bridging theoretical knowledge with real-world environmental applications and fostering students' critical thinking and problem-solving skills.